Cardiovascular toxicity of the treatment of oncological diseases in children and adolescents: Position paper on aspects of cardiological care and aftercare Kardiovaskuläre Toxizität der Therapie onkologischer Erkrankungen bei Kindern und Jugendlichen: Positionspapier zu Aspekten der kardiologischen Betreuung und Nachsorge - Neudorf, Ulrich; Schönecker, Anne; Apitz, Christian; Koch, Dieter; Voges, Inga; Rassaf, Tienush; Langer, Thorsten; Reinhardt, Dirk; Zolk, Oliver; Schöber, Martin (Monatsschrift Kinderheilkunde, 2023)
Children and adolescents survive a diagnosis of cancer and successful cancer treatment longer than adults; therefore, delayed sequelae of treatment, such as cardiotoxic long-term effects, become increasingly more relevant. Anthracyclines are frequently used in oncological treatment and their acute and chronic cardiotoxicity is well known. They are used in approximately 60% of cancer treatments and are currently the chemotherapeutic agents with the quantitatively highest risk for cardiotoxicity. Other newer drugs and irradiation are an additional sometimes unknown risk for the heart and blood vessels. Apart from cardiomyopathy, this also includes the occurrence of systemic and pulmonary artery hypertension. The risk of late cardiovascular sequelae due to radiotherapy is becoming increasingly better characterized. Some of the undesired side effects occur first during the course of time, long after the initial treatment of the patients. The delayed sequelae for the heart can initially remain clinically concealed, although a subclinical left ventricular systolic dysfunction is already present. The manifestation of heart failure follows later; however, then the patients are no longer under the care of physicians for pediatrics and adolescent medicine, have reached adulthood and should be under the care of physicians for adults. A structured transition after oncological treatment is therefore essential. In recent years some position papers or guidelines on the topic of cardio-oncology have been published but the pediatric aspect has received little attention. The aim of this position paper is to increase the attention of pediatric cardiologists and oncologists as well as cardiologists and oncologists for adults with respect to this topic. Risk factors for cardiovascular toxicity of the various diseases and treatment protocols are presented and the state of knowledge on avoidance of toxicity and manifest heart failure are described. The focus is on the type and performance of cardiological diagnostics and aftercare.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Anthracyclines; Cardio-oncology; Risk factors; Screening; Transition to adult care